Linearization of High Power Amplifier Using Modified Artificial Bee Colony and Particle Swarm Optimization Algorithm. (2016) - Bipin, P.R.; Rao, P.V.
Abstract: A linearization method for power amplifiers is proposed to cancel out distortion induced during amplification. Wiener model is chosen for power amplifier modelling. The linearization is achieved by the Modified Artificial Bee Colony (ABC) and Particle Swarm Optimization (PSO) algorithm. The Modified ABC and PSO algorithm reduces the complexity in linearization. Experimental results obtained for the proposed method shows that a better linearization of the amplifier characteristics can be obtained using the proposed method.